Called into the Mission of God : A Missional Reading of Paul's Thessalonian Correspondence - George, Roji T. (Book collections on Project MUSE., 2020)
In Called into the Mission of God, Roji George argues that Paul's primary interest was neither doctrinal teaching nor the articulation of an anti-imperial discourse. Instead, he contends that amidst the many problems that faced the local Thessalonian community--problems arising out of eschatological fears, ethical difficulties in the community, and persecution from outside groups--Paul brought primarily a missional concern to impart ethical exhortation and eschatological teaching in a political language. The book will be helpful to those theologians, scholars, teachers, and students grappling with the message of Paul in his own time and in ours. Called into the Mission of God represents an increasing commitment on the part of Fortress Press to support the wide dissemination of the best theological and biblical writing by the best scholars from the Global South.